A Rare Case of Spontaneous Cardiac Tamponade Induced by Concomitant Use of Rivaroxaban and Amiodarone - Oreoluwa Oladiran; Jared Segal; Ifeanyi Nwosu; Salik Nazir (Case Reports in Cardiology)
Rivaroxaban is a direct oral anticoagulant (DOAC) approved as an important alternative to warfarin in patients with nonvalvular atrial fibrillation. We report the case of an 87-year-old man with past medical history of nonvalvular atrial fibrillation on rivaroxaban and recently started amiodarone for pulseless ventricular tachycardia who presented to our hospital with intermittent chest pain and was diagnosed with spontaneous hemopericardium causing cardiac tamponade. The culprit drugs were discontinued, and the patient was treated with emergent pericardiocentesis. Both rivaroxaban and amiodarone are substrates for the CYP3A4 hepatic pathway, and concomitant use can result in increased plasma rivaroxaban levels causing an increased propensity to bleeding. While most physicians are cognizant of the need for renal dosing of rivaroxaban, this article aims to increase awareness of its interactions with drugs that are also metabolized through the same hepatic CYP450 pathway.